Ethnic elites and rituals of provocation: politicians, pastors, and paramilitaries in Northern Ireland - Blake, Jonathan S. (Terrorism and political violence, 2019)
Prominent theories of ethnic conflict argue that instrumental ethnic elites incite violence in order to promote their own power. Yet this approach focuses primarily on political leaders and ignores other ethnic elites, meaning that we know little about how other influential actors think about provocation. In this paper, I present novel data from Northern Ireland on diverse elite attitudes toward polarising Protestant parades with a long history of sparking ethnic violence. Using original surveys of Protestant elected officials and clergy as well as interviews with ex-paramilitaries, this paper demonstrates that these elite groups have different, often competing, interests and opinions regarding contested parades: while politicians tend to support provocative parades, the others do not. By addressing elite actors that are often ignored, I present a more nuanced picture of elite-mass relations and ethnic mobilisation in conflict.